2011
DOI: 10.1021/om200735c
|View full text |Cite
|
Sign up to set email alerts
|

Gold Catalysis: Hydrolysis of Di(alkoxy)carbenium Ion Intermediates as a Sensor for the Electronic Properties of Gold(I) Complexes

Abstract: Six different cationic gold(I) complexes LAu+ were converted to the corresponding di(alkoxy)carbenium ions by reaction with ethyl 2,5-dimethylhexa-2,3-dienoate. These conversions were monitored by in situ IR spectroscopy; at room temperature they proceeded in only a few seconds. The ligands L are based on the most popular ligand types in gold catalysis: phosphanes, phosphites, carbenes, and isonitriles. The di(alkoxy)carbenium ions were stable, not short-lived intermediates, and could be characterized. This al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…This result illustrates the uniqueness of our catalytic system and that remarkably active heterogeneous single‐site catalysts can be prepared. Because the electronic properties of the phosphine ligands strongly influence the activity of the corresponding Au I complexes, further fine‐tuning of the properties of the solid ligand is also possible 30…”
Section: Methodsmentioning
confidence: 99%
“…This result illustrates the uniqueness of our catalytic system and that remarkably active heterogeneous single‐site catalysts can be prepared. Because the electronic properties of the phosphine ligands strongly influence the activity of the corresponding Au I complexes, further fine‐tuning of the properties of the solid ligand is also possible 30…”
Section: Methodsmentioning
confidence: 99%
“…( b ) Comparison of related bond lengths and characteristic NMR spectroscopic data of complex 8 with those of reference complexes 15 and 15a ; see ref. 63. ( c ) Comparison of Mayer bond order of complex 8 with those of reference complexes 14 and 15 ; see refs 63 and 62.…”
Section: Figurementioning
confidence: 99%
“…Guided by the work of Müller, [15][16][17][18][19] we recently reported that low-temperature hydride abstraction from the gold acetylide complex 12 a with triphenylcarbenium tetrakis(pentafluorophenyl)borate leads to selective formationo ft he thermally unstable cationic gold (b,b-disilyl)vinylidene complex 13 a (Scheme 5). [20,21] Key to characterization of 13 a were resonances at d = 206 and 112i nt he 13 CNMR spectrum assigned to the C1 and C2 vinylidene carbon atoms, respectively ( Table 1). Also noteworthy was the significant decrease in the one-bond C1ÀC2 coupling constant of 13 a ( 1 J CC = 60 Hz) relative to the acetylide precursor 13 a ( 1 J CC = 91 Hz; D 1 J CC = 31 Hz)c onsistent with the diminished s-charactero ft he C2 atom of 13 a relative to 12 a.…”
Section: Cationicgold (Bb-disilyl)vinylidenecomplexesmentioning
confidence: 99%
“…To this end, we synthesized the thermally unstable gold (b,b-disilyl)vinylidene complexes [(L)Au = C = CSi(Me) 2 ]CH 2 CH 2 Si(Me) 2 + B(C 6 F 5 ) 4 À [L = IPr (13 b), IMes (13 c), SIPr (13 d), SIMes (13 e)],w hich contain an NHC ligand, by employing procedures similart ot hose used to synthesize 13 a.C onversely, attempted synthesis of gold (b,b-disilyl)vinylidene complexes containing lesse lectron-donating ligandssuch as PPh 3 provedu nsuccessful. The thermally unstablec omplexes 13 b-e werec haracterized withouti solation by low temperature 1 H, 13 C, and 29 Si NMR spectroscopy ( Table 1). The 13 CNMR spectra of complexes 13 b-e displayed vinylidene C1 and C2 resonances at d = 203-198 ppm and d = 112-115 ppm, respectively (Table 1), which, in contrastt ot hose of 13 a,d isplayed no broadening at À80 8C.…”
Section: Cationicgold (Bb-disilyl)vinylidenecomplexesmentioning
confidence: 99%